2020
DOI: 10.1097/sap.0000000000002321
|View full text |Cite
|
Sign up to set email alerts
|

Is the Glass-Ceiling Higher Than We Think? Sex Disparity Trends in Physician Executive Positions and Academic Plastic Surgery

Abstract: Introduction Advanced levels of professorship and executive positions are considered markers of success in medical academia. Despite sex parity in medical school graduates, sex disparities within positions of power remain unequal. The purpose of this study was to analyze sex composition at different levels of leadership at multiple academic, highly ranked institutions. Methods Hospital executives and academic plastic surgery faculty were identified thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Between 2008 and 2018, there was a great increase in both the number of women entering plastic surgery training, as well as tremendous growth in the number of women in plastic surgery leadership positions 19 . Previous research has also shown that sex representation in plastic surgery departments favors male surgeons, and that there is a paucity of women in leadership roles 20,21 . One report analyzing the representation of women in plastic surgery, found that they were underrepresented in academic medicine and leadership roles across regional and national organizations 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Between 2008 and 2018, there was a great increase in both the number of women entering plastic surgery training, as well as tremendous growth in the number of women in plastic surgery leadership positions 19 . Previous research has also shown that sex representation in plastic surgery departments favors male surgeons, and that there is a paucity of women in leadership roles 20,21 . One report analyzing the representation of women in plastic surgery, found that they were underrepresented in academic medicine and leadership roles across regional and national organizations 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Workplace diversity is known to decrease among positions with increasing seniority or leadership [44][45][46] ; this is especially evident in many competitive surgical specialties, including PRS. [47][48][49][50][51] Although women make up 43.5% of all PRS residents, their proportion drops to 17.2% of practicing plastic surgeons, 13% of program directors, and only 8% of department chairs. 16,49,52 These numbers drop further for women of color, who occupy only 6.25% of PRS program leadership roles.…”
Section: Gendermentioning
confidence: 99%
“…There are no female editors in chief of plastic surgery journals. 14 This lack of visible female leadership is witnessed by students, residents and even faculty creating a self-sustaining cycle of lack of representation. 13 Our proposed solution is to elect a woman as an editor in chief.…”
Section: Boldness In Academic Plastic Surgerymentioning
confidence: 99%
“…14 What began as one woman’s accidental acceptance to medical school from a practical joke, has transformed into women comprising more of the medical school class than men. 14 Women are no longer accepting previous constraints. In her book published in 1949 Simone de Beauvoir said “It is perfectly natural for the future woman to feel indignant at the limitations posed upon her by her sex.…”
Section: Boldness In Academic Plastic Surgerymentioning
confidence: 99%